Cardiorespiratory fitness levels in Malaysian women - Nordin, N.A.M.M.; Husain, R.; Karim, A.A.H.; Ali, O. (Japan Int Cultural Exchange Foundation, 2010)
Objective: To determine the factors that influence cardiorespiratory fitness (CRF) among Malay and Chinese Malaysian women. Methods: Age, ethnicity, height and waist circumference were the predictors of a non-exercise CRF regression model developed for healthy Malaysian women aged 20-64 years. Further comparisons between the two ethnic groups were done on their sociodemographic, biophysical, physical activity, dietary and mental health profile to elucidate the differences which contribute to CRF. Results: For the same age group, Chinese women had higher levels of CRF. They were lighter in terms of weight and body mass index and also had smaller waist and hip circumferences. Both systolic and diastolic blood pressures were lower. They were better educated, majority were single and those that were married had fewer numbers of children. They spent more time on exercise while dietary habits were similar. No significant differences were seen in the levels of stress, anxiety and depression. Conclusion: The higher level of exercise among the Chinese women may contribute to the higher CRF and better body composition as supported by other studies. Their higher level of education may also influence greater participation in exercise.